2020
DOI: 10.3389/fpls.2020.01113
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperatures Impose Transcriptional Constraints and Elicit Intraspecific Differences Between Coffee Genotypes

Abstract: The projected impact of global warming on coffee production may require the heatadapted genotypes in the next decades. To identify cellular strategies in response to warmer temperatures, we compared the effect of elevated temperature on two commercial Coffea arabica L. genotypes exploring leaf physiology, transcriptome, and carbohydrate/protein composition. Growth temperatures were 23/19°C (day/night), as optimal condition (OpT), and 30/26°C (day/night) as a possible warmer scenario (WaT). The cv. Acauã showed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 103 publications
(149 reference statements)
2
15
0
Order By: Relevance
“…Genome assembly of the allotetraploid C. arabica supports a high level of genetic sharing with the diploid progenitors, C. canephora and C. eugenioides [ 20 ]. Comparative studies between coffee species and genotypes are scarce, but the few existing ones are in line with our findings and suggest some common responses to supra-optimal temperatures [ 36 , 41 , 47 ] and a bottleneck effect in transcriptional activation at warmer temperatures [ 35 ]. On the other hand, eCO 2 increased the numbers at 42 °C in both genotypes ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Genome assembly of the allotetraploid C. arabica supports a high level of genetic sharing with the diploid progenitors, C. canephora and C. eugenioides [ 20 ]. Comparative studies between coffee species and genotypes are scarce, but the few existing ones are in line with our findings and suggest some common responses to supra-optimal temperatures [ 36 , 41 , 47 ] and a bottleneck effect in transcriptional activation at warmer temperatures [ 35 ]. On the other hand, eCO 2 increased the numbers at 42 °C in both genotypes ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 85%
“…These DEGs are probably critical for enhancing temperature tolerance in Icatu and CL153, in contrast with other varieties of C. arabica (cv. Acauã and Catuaí) where the number of DEGs decreased as a response to elevated temperatures (23/19 °C vs. 30/26 °C [ 35 ]). Nevertheless, these differences might also be due to the short period of the experimental trial (e.g., 4 weeks [ 35 ] vs. 10 months in our present study), and to the physiological performance of coffee plants which is frequently higher at 30 °C than at 25 °C [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are explained by the allopolyploidy of C. arabica , which promotes an evolutionary advantage in having additional genetic materials that attribute greater plasticity in coping with environmental variations compared with its parentals—in this case, C. canephora and C. eugenioides . In other words, the allopolyploidy of C. arabica makes this species able to up and downregulate certain genes responsible to keep the homeostasis during low temperatures, as reported by Bardil et al (2011) , or even at higher temperatures ( de Oliveira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the optimal annual mean temperature range was stated as 18–21 °C for arabica cultivars [ 50 ]. In this way, it was reported that mean air temperatures above 23 °C could accelerate fruit ripening of arabica cultivars, which can cause bean quality loss, and seasonal high temperatures above 33 °C and dryer seasons can greatly reduce floral initiation and increase the production of abnormal reproductive structures, and flower abortion [ 51 , 52 , 53 , 54 ]. However, current Arabica cultivars can grow in marginal regions, such as in the northeast of Brazil, where the mean annual temperature can reach 25 °C [ 55 ], and elite cultivars can successfully withstand relatively high temperatures [ 12 , 34 ] to a greater extent than traditionally assumed in classical studies [ 56 ].…”
Section: Introductionmentioning
confidence: 99%